A infiltração policial como instrumento de combate aos delitos perpetrados por organizações criminosas - Lameirão, Claudio Marcos Romero (2015)
A this work has as main purpose the analysis and the study of one of the most auspicious and complex, given the absence of a uniform legislative treatment, in terms of its definition, modalities, constitutional and conventional compatibility and limits of operation, means investigation and evidence collection called Police Infiltration (Infiltration Police) as instrument to combat criminal organizations. Thus, it seeks to preliminarily carry out an approach about organized crime from its historical evolution, passing, moreover, by his paternal legislative development and leaving clairvoyant mister of a precise legal definition of the concept. Addresses is also the theme of the evidence within the general theory of the process, analyzing their concept and the difference between proof and means of obtaining evidentiary materials, so we can leave for the study of the central axis of this work, which is the Infiltration Officer, in light of their circumstances and inability to be used in obtaining evidence relating to any criminal offense, because our legislation restrict it to specific situations, authorized by the magistrate. Then analyzes the police infiltration, with particular emphasis on its historical aspects, concepts and scopes, the differences between the undercover agent and the provocative, their treatment in the right of parental rights plan and their designs in the Palermo Convention, which is the main document international fight against transnational organized crime. Wanted also check who can act as undercover agent, if any individual or police and even the latter category, if any corporation or only those who are authorized to function as an investigative police, according to the paternal law in force in order that the convention mentioned above is silent on this point. For last, there was a brief analysis of this institute in the US legislation, to have arisen in that country organized crime expression, Portugal, for having one of the most modern legislation, with regard to its combat and Colombia, because it is one of the largest players in the international drug trafficking, with the aim of demonstrating the establishment of rules in these countries, in view of the criminological characteristics of each one.